Validity of the polymerase chain reaction in the diagnosis of clinically suspected cases of American visceral leishmaniasis - Celia Maria Silva Pedrosa; Ricardo Arraes de Alencar Ximenes; Wendell Alexandre Pinheiro de Almeida; Eliana Maria Mauricio da Rocha (Brazilian Journal of Infectious Diseases)
To test the validity of the polymerase chain reaction for diagnosing American visceral leishmaniasis, 88 suspected cases were studied. Diagnosis was confirmed in 47 (53.5%) and ruled out in 41 (46.5%) patients. Samples of bone marrow and peripheral blood were processed by polymerase chain reaction to evaluate the sensitivity and specificity of the test and its agreement beyond chance with microscopy examination. The polymerase chain reaction was positive in bone marrow of 100% of the patients with amastigotes seen with microscopy examination, and in 59.5% in those where no parasite were seen. Agreement beyond chance between visualization of the parasite in bone marrow aspirates and polymerase chain reaction was considered weak (Kappa = 0.41). Concordance between polymerase chain reaction of bone marrow aspirates and of peripheral blood was considered excellent (Kappa = 0.88). The test turned out positive in all bone marrow aspirates of those with the disease and whereas the positivity rate was 58.5% among those without the disease, with specificity rate of 41.5%.